KONTRUKS PEMIKIRAN PENDIDIKAN ISLAM WAWASAN MASA DEPAN - Mohammad Afiful Hair (Fakultas Agama Islam Universitas Islam Madura, 2021)
Globalization is inevitable. Therefore, in order for Islamic education to be a role in the global community, Peru is observed and reconsidered the philosophy, theory, and curriculum of Islamic education today. The construct of future-minded Islamic education thinking needs to be directed at improving efforts to answer the problems of ontemporer life, and stick to the nlai-niai ajara al-Qur'an and Sunnah. The values and moral content of the Qur'an and sunnah must be transformed to students in the face of modern life in society. The strategic thing lies not only in the ability to respond to global change, but more importantly the ability to frame any change in the moral frame of the Qur'an and sunnah. Thus, the task of Islamic educational institutions is to integrate between religious subjects and secular subjects in the learning package. With the integration of science with islamic teaching values, it is no longer known the term religious science and general science but will be distinguished into sciences that concern tanziliyah verses and knowledge about kauniyah verses.